IBM Storwize HyperSwap with IBM i - Jamsek, Jana; Schneider, Falk (IBM Corporation, International Technical Support Organization, 2018)
IBM® Storwize® HyperSwap® is a response to increasing demand for continuous application availability, minimizing downtime in the event of an outage, and non disruptive migrations. IT centers with IBM i can take full advantage of the HyperSwap solution. In this IBM Redpaper™ publication, we provide instructions to implement Storwize HyperSwap with IBM i. We also describe some business continuity scenarios in this area, including solutions with HyperSwap and IBM i Live Partition Mobility, and a solution with HyperSwap and IBM PowerHA® for IBM i.
"Storage.". - Number on back cover: REDP-5490-00. - Online resource; title from cover (Safari, viewed October 9, 2019)
Keywords: Storage area networks (Computer networks); Information storage and retrieval systems; Information Systems; Réseaux de stockage (Informatique); Systèmes d'information